Part A:
To factor the equation \(12x^2 - 18x = 0\), we first find the Greatest Common Factor (GCF) of the two terms. The GCF of \(12x^2\) and \(-18x\) is \(6x\).
Now, we can factor this out:
\[ 12x^2 - 18x = 6x(2x - 3) = 0 \]
So the correct option is:
6x(2x - 3) = 0
Part B:
To find the solutions, we set each factor equal to zero:
- \(6x = 0\) implies \(x = 0\).
- \(2x - 3 = 0\) implies \(2x = 3\) or \(x = \frac{3}{2}\).
Thus, the two solutions are:
x = 0 and x = \frac{3}{2}
So the corresponding response is:
x = 0 and x = \frac{3}{2}.